Listening the Costa Rican diversity: status of the bioacoustics collection of the Museum of Zoology, University of Costa Rica - Alvarado-Deckwart, Montserrat (2025)
Introduction: Bioacoustic collections maintain, curate, and preserve animal sounds gathered by biologists and naturalists, serving as valuable archives of the planet's acoustic biodiversity. These collections facilitate the study of species behavior, distribution, and ecology. These collections provide valuable information for the conservation of endangered species and habitats. Objective: This study describes the current status of the Bioacoustics Collection at the Museum of Zoology, CIBET, University of Costa Rica. Methods: We reviewed the 4,366 recordings cataloged in the collection, and provided information on their distribution across taxonomic groups, and on the specific geographic locations within Costa Rica where they were obtained. We also discuss the importance of this collection as a key repository for bioacoustics research both nationally and internationally. Results: The collection predominantly comprises bird recordings, representing approximately 58.15% of Costa Rica's avian species. Additionally, the collection includes recordings of other groups, such as amphibians and mammals. Conclusions: The analysis revealed the importance of the collection for scientific research, conservation, and environmental education. This collection outstands as a vital resource for future bioacoustic research in Costa Rica and beyond. It also highlights the need to enhance the representation of other taxonomic groups and invites researchers to contribute to this repository, as a source for a better understanding the acoustic diversity and support conservation efforts.